Optimal Control of a Production Process Subject to Random Deterioration - Schneider, Helmut; Tang, Kwei; O'Cinneide, Colm (Operations research, 1990)
A production process exhibits a decreasing pattern in the process mean in the course of production. We address the decision problem of selecting the starting level of the process mean and the level at which the process mean should be adjusted back to the starting level. The costs to be minimized are the long-run average cost of production, adjustment and loss for defective items. In addition to the optimal solution, simple approximate solutions are developed and shown to be more cost effective than a simple linear policy often applied to this problem.